Polypragmasia in the therapy of infected wounds – conclusions drawn from the perspectives of low temperature plasma technology for plasma wound therapy - Kramer, Axel (German Medical Science GMS Publishing House, 2008)
As long as a wound is infected, the healing process cannot begin. The indication for wound antiseptic is dependent on the interaction between the wound, the causative micro-organisms, and the host immune system. An uncritical colonisation is a condition whereby micro-organisms on a wound will proliferate, yet the immune system will not react excessively. Wound antiseptic is most often not necessary unless for epidemiologic reasons like colonisation with multi-resistant organisms. In most instances of a microbial contamination of the wound and colonisation, thorough cleaning will be sufficient. Bacterial counts above 10(5) to 10(6) cfu per gram tissue (critical colonisation) might decrease wound healing due to release of toxins, particularly in chronic wounds. Traumatic and heavily contaminated wounds therefore will require anti-infective measures, in particular wound antiseptic. In such situations, even a single application of an antiseptic compound will significantly reduce the number of pathogens, and hence, the risk of infection. If a wound infection is clinically manifest, local antiseptics and systemic antibiotics are therapeutically indicated. The prophylactic and therapeutic techniques for treatment of acute and chronic wounds (chemical antiseptics using xenobiotics or antibiotics, biological antiseptic applying maggots, medical honey or chitosan, physical antiseptic using water-filtered infrared A, UV, or electric current) mostly have been empirically developed without establishing a fundamental working hypothesis for their effectiveness. The most important aspect in controlling a wound infection and achieving healing of a wound is meticulous debridement of necrotic material. This is achieved by surgical, enzymatic or biological means e.g. using maggots. However, none of these methods (with some exception for maggots) is totally gentle to vital tissue and particularly chemical methods possess cytotoxicity effects. Derived from the general principles of antiseptic wound treatment, the following working hypothesis is postulated: the most ideal constellation for treatment of wounds is the superficial destruction of microbial layers without deep tissue alteration, like it is caused by antiseptics, in order not to endanger the regenerative granulation tissue. At the same time, it is desirable to support and increase cell proliferation and granulation capacities. These two aspects might be achieved by using low temperature plasma technology.